2010
DOI: 10.1111/j.1365-2923.2010.03742.x
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional visualisation improves understanding of surgical liver anatomy

Abstract: This study showed that 3-D imaging significantly improved the identification of complex surgical liver anatomy. Male students benefited significantly more than female students from 3-D presentations. Use of colour in 3-D presentation did not improve student performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 21 publications
1
51
0
1
Order By: Relevance
“…Several recent publications have examined the value of multimedia tools for medical instruction with controlled experiments. The results of these studies have varied, with some studies concluding that there is a distinct educational benefit from higher technology instruction (Hallgren et al, 2002;Hudson, 2004;Prinz et al, 2005;Nicholson et al, 2006;Beranova and Sykes, 2007;Jurgaitis et al, 2008;Beermann et al, 2010;Estevez et al, 2010), while others have found that these modules offer no benefit, or that traditional methods of instruction are superior (Garg et al, 2002;Hariri et al, 2004;Mayer et al, 2005;Huk, 2006;Levison, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent publications have examined the value of multimedia tools for medical instruction with controlled experiments. The results of these studies have varied, with some studies concluding that there is a distinct educational benefit from higher technology instruction (Hallgren et al, 2002;Hudson, 2004;Prinz et al, 2005;Nicholson et al, 2006;Beranova and Sykes, 2007;Jurgaitis et al, 2008;Beermann et al, 2010;Estevez et al, 2010), while others have found that these modules offer no benefit, or that traditional methods of instruction are superior (Garg et al, 2002;Hariri et al, 2004;Mayer et al, 2005;Huk, 2006;Levison, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to increase safe right lateral sector LDLT and to overcome donor shortage, accurate preoperative anatomical evaluation and excellent surgical technique coping with the particular anatomical variants are required. Anatomical understanding based on the 2D images is not sufficient 8) . The understanding of the 3D vascular and biliary anatomy will contribute to a better definition of the anatomical contraindications for transplantation, and to achieve successful right lateral sector LDLT.…”
Section: Resultsmentioning
confidence: 99%
“…44 Other studies randomized medical students to different educational modalities to determine how students most effectively learn to use proper pressurized metered dose inhalers 45 and to recognize agonal breathing as a sign of cardiac arrest. 46 As a final example, randomized controlled studies in gastroenterology have assisted in ascertaining the effects of various educational experiences, including: 3D visualizations on learning of liver anatomy, 47,48 role-playing and simulations in the learning of digital rectal exam, 49 and abdominal ultrasound training in learning the physical examination of the abdomen. 50 Further studies assess the value of computer-aided learning on student understanding of the anatomy and physiology of the liver and biliary tree, 51 as well as the influence of peer teaching on students' knowledge acquisition and retention in a gastroenterology/hematology course.…”
Section: Discussionmentioning
confidence: 99%